High-plasticity Mo-Ce impact energy release alloy and preparation method thereof
Through the design of Mo metal frame and Ce fill structure of Mo-Ce alloy, the problem of insufficient density and plasticity of existing impact energy-release alloys is solved, high density and excellent dynamic compression performance are achieved, and application requirements in the energy and military fields are met. .
Patent Information
- Application Number
- CN202411448438.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-14
AI Technical Summary
The existing impact energy release alloys have high crushing rate under explosive drive, poor kinetic energy penetration ability, and small dynamic failure strain, which cannot meet the requirements of high density, high strength and good plasticity.
Mo-Ce alloy is adopted to prepare high-density Mo-Ce impact energy release alloys through the structural design of Mo metal frame and Ce filling, and use cold isostatic pressing and sintering technology to ensure good interface wetting of Mo and Ce and High plasticity, achieving high density and excellent dynamic compression performance of alloys.
It has achieved high density, quasi-static compression strength greater than 600MPa, quasi-static plasticity greater than 40%, dynamic compression strength greater than 700MPa, and dynamic plasticity reaching 29% to 33%, significantly improving the material's overload resistance and kinetic energy damage ability.
Smart Images

Figure CN119307797A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energetic materials, and in particular to a high-plasticity Mo-Ce impact energy-releasing alloy and a preparation method thereof. Background Art
[0002] In recent years, new impact energy release alloys with both kinetic energy and chemical energy have received extensive attention. A large number of studies have been conducted on impact energy release tungsten alloys such as W-Zr and W-Zr-Hf. Although these alloys have high density and strength, they have a large amount of brittle W 2 Zr intermetallic compounds inhibit the activity of Zr elements, resulting in poor chemical energy release effect of the material. At the same time, the brittle phase causes low plasticity of the alloy, high crushing rate under explosive driving, and reduced kinetic energy penetration ability. In addition, studies have shown that W-Zr-Ti, W-Zr-Ti-Nb and other systems can inhibit W 2 The formation of Zr intermetallic compounds enables Zr to exist in the form of solid solution atoms and maintain energy release activity, but the dynamic failure strain of the alloy is still less than 10%.
[0003] Metal Ce has a face-centered cubic structure, good plasticity, high oxidation heat value and energy release activity, and Ce and W do not form intermetallic compounds, which can avoid the reduction of alloy plasticity caused by brittle phase. Studies have found that W-Ce alloy has excellent dynamic compressive strength and plasticity, but its quasi-static plasticity is only 17%, which has great limitations in practical applications. Summary of the invention
[0004] The purpose of the present invention is to provide a high-plasticity Mo-Ce impact energy-releasing alloy and a preparation method thereof. The Mo-Ce impact energy-releasing alloy provided by the present invention has high density, high strength and good plasticity, and meets the application requirements of energetic materials in the fields of energy, military industry, etc.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a high-plasticity Mo-Ce impact energy release alloy, comprising a Mo metal skeleton and Ce filled in the Mo metal skeleton, wherein the mass fraction of Mo in the high-plasticity Mo-Ce impact energy release alloy is 50-95%, and the mass fraction of Ce is 5-50%.
[0007] Preferably, the density of the Mo metal skeleton is 7.5 to 9.5 g / cm 3 , the density is 73~93%.
[0008] Preferably, the density of the high plasticity Mo-Ce impact energy release alloy is 8-10 g / cm 3 , density is greater than 97%.
[0009] The present invention also provides a method for preparing the high-plasticity Mo-Ce impact energy release alloy described in the above technical solution, comprising the following steps:
[0010] 1) Pressing Mo metal powder into a shape to obtain a green body;
[0011] 2) sintering the green body obtained in step 1) to obtain a Mo metal skeleton;
[0012] 3) Infiltrating pure Ce with the Mo metal skeleton obtained in step 2) to obtain a high-plasticity Mo-Ce impact energy release alloy.
[0013] Preferably, in step 1), the particle size of the Mo metal powder is 5-10 μm.
[0014] Preferably, the pressing in step 1) adopts a cold isostatic pressing process, the pressure of the cold isostatic pressing process is 150-400 MPa, and the holding time is 5-30 min.
[0015] Preferably, in step 2), the sintering temperature is 1200-1800° C., and the holding time is 2-6 hours.
[0016] Preferably, the infiltration in step 3) is carried out under vacuum conditions with a vacuum degree less than 1Pa.
[0017] Preferably, the infiltration temperature in step 3) is 800-1300° C., and the insulation time is 0.5-3 h.
[0018] Preferably, the infiltration in step 3) is performed by step heating; the step heating method is to first heat the temperature to 700°C at a rate of 6-10°C / min, and then heat the temperature to the infiltration temperature at a rate of 1-3°C / min.
[0019] The present invention provides a high-plasticity Mo-Ce impact energy release alloy, comprising a Mo metal skeleton and Ce filled in the Mo metal skeleton, wherein the mass fraction of Mo in the high-plasticity Mo-Ce impact energy release alloy is 50-95%, and the mass fraction of Ce is 5-50%. The present invention uses Mo as a skeleton, fills the pores of the Mo skeleton with Ce, and wraps the Mo skeleton, thereby being able to coordinate the deformation of the Mo skeleton during deformation and reduce stress concentration, so that the alloy has higher density, strength and excellent plasticity; compared with W-Ce alloy, the Mo-Ce alloy provided by the present invention has better plasticity. The results of the embodiments show that the density of the high-plasticity Mo-Ce impact energy release alloy provided by the present invention is 7-10g / cm 3, the density reaches more than 97%, the quasi-static compression strength is greater than 600MPa, the quasi-static plasticity is greater than 40%, the dynamic compression strength is greater than 700MPa, and the dynamic plasticity reaches 29% to 33%. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM image of the high plasticity Mo-Ce impact energy release alloy prepared in Example 2;
[0021] Figure 2 quasi-static compressive stress-strain curves of the high plasticity Mo-Ce impact energy release alloys in Examples 1 to 4;
[0022] Figure 3 The dynamic compression true stress-strain curves of the high plasticity Mo-Ce impact energy release alloy in Examples 1 to 3. DETAILED DESCRIPTION
[0023] All raw materials of the present invention have no particular limitation on their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0024] The invention provides a high-plasticity Mo-Ce impact energy release alloy, comprising a Mo metal skeleton and Ce filled in the Mo metal skeleton, wherein the mass fraction of Mo in the high-plasticity Mo-Ce impact energy release alloy is 50-95%, and the mass fraction of Ce is 5-50%.
[0025] In the present invention, the mass fraction of Mo in the high plasticity Mo-Ce impact energy release alloy is 50% to 95%, preferably 60% to 95%, more preferably 70% to 95%, and further preferably 80% to 95%.
[0026] In the present invention, the mass fraction of Ce in the high plasticity Mo-Ce impact energy release alloy is 5% to 50%, preferably 5% to 40%, more preferably 5% to 30%, and further preferably 5% to 20%.
[0027] In the present invention, the density of the Mo metal skeleton is preferably 7.5 to 9.5 g / cm 3 The density is preferably 73-93%. The Mo metal skeleton is the basis of the Mo-Ce alloy. The density of the Mo metal skeleton is within the above range. The Mo metal skeleton has a certain strength and ensures a uniform and connected pore distribution, which is conducive to the filling of Ce.
[0028] In the present invention, the density of the high plasticity Mo-Ce impact energy release alloy is preferably 8 to 10 g / cm 3, the density is preferably greater than 97%. The service environment of impact energy release structural materials is usually high stress and high strain rate loading conditions, and micropores will lead to aggravated localized deformation of the material, which is the main factor for the failure of the material under dynamic loading conditions. Therefore, the material needs to have a higher density to improve its overload resistance; in addition, high density is a key factor to ensure the release of kinetic energy of the material. In the present invention, the density and density of the Mo-Ce alloy are within the above range, which can significantly improve the material's overload resistance and kinetic energy damage capability.
[0029] The Ce in the Mo-Ce impact energy release alloy provided by the present invention exists in a single substance form, which can maximize the impact energy release activity of the Ce element; in addition, the Mo in the material has a body-centered cubic structure and the Ce has a face-centered cubic structure, both of which have high plasticity and good interface wettability, which enables the material to have high plasticity. On the one hand, this can ensure the high overload resistance of the material under shock wave loading conditions, and on the other hand, it is beneficial for it to accumulate plastic deformation work during high-speed impact to obtain high temperature rise, which is convenient for subsequent sufficient oxidation energy release.
[0030] The present invention also provides a method for preparing the high-plasticity Mo-Ce impact energy release alloy described in the above technical solution, comprising the following steps:
[0031] 1) Pressing Mo metal powder into a shape to obtain a green body;
[0032] 2) sintering the green body obtained in step 1) to obtain a Mo metal skeleton;
[0033] 3) Infiltrating pure Ce with the Mo metal skeleton obtained in step 2) to obtain a high-plasticity Mo-Ce impact energy release alloy.
[0034] The present invention compresses Mo metal powder into a shape to obtain a green compact.
[0035] In the present invention, the Mo metal powder is preferably high-purity Mo metal powder, and the purity of the high-purity Mo metal powder is preferably greater than 99.95%.
[0036] In the present invention, the particle size of the Mo metal powder is preferably 5 to 10 μm. In the present invention, the Mo metal powder is preferably screened before use; the screening preferably uses a sieve, and the mesh number of the sieve is preferably 500 to 1000 meshes. By screening the Mo metal powder, larger Mo particles can be filtered out, so that the pore distribution of the pressed green body is uniform, which is conducive to the subsequent filling of Ce.
[0037] The present invention has no special requirements on the pressing and forming equipment, as long as the Mo metal powder can be pressed into a green body.
[0038] In the present invention, the press molding preferably adopts a cold isostatic pressing process, and the pressure of the cold isostatic pressing process is preferably 150 to 400 MPa, and more preferably 150 to 300 MPa. The pressure of the press molding affects the density of the green body. The greater the pressure, the greater the density of the green body. However, when the pressure exceeds 400 MPa, a large number of closed pores will be formed in the green body, thereby reducing the density of the green body.
[0039] In the present invention, the holding time of the cold isostatic pressing process is preferably 5 to 30 minutes, more preferably 10 to 30 minutes. The holding time of compression molding affects product quality and performance. In the present invention, the holding time is limited to the above range to obtain a green body with high density and uniform pore distribution.
[0040] After obtaining the green compact, the present invention sintered the green compact to obtain a Mo metal skeleton.
[0041] The present invention has no special requirements for the sintering equipment, as long as it can sinter the green body. The present invention is preferably a sintering furnace.
[0042] In the present invention, the sintering temperature is preferably 1200-1800°C, more preferably 1200-1600°C. The sintering temperature affects the density of the Mo metal skeleton, and thus affects the strength and plasticity of the alloy. When the temperature is lower than 1200°C, the Mo-Mo interface bonding is relatively poor, which is not conducive to improving the density of the Mo metal skeleton; as the temperature increases, more sintering necks will be formed in the skeleton, and the contact area of the Mo particles will increase, which is conducive to improving the density of the Mo metal skeleton; when the temperature exceeds 1800°C, a large number of closed pores will be formed in the skeleton, and the molten metal Ce will not be able to enter the pores for filling, which will reduce the density of the Mo metal skeleton. The present invention limits the sintering temperature within the above range, which can further improve the density of the Mo metal skeleton, and thus improve the strength and plasticity of the alloy.
[0043] In the present invention, the sintering holding time is preferably 2 to 6 hours, more preferably 2 to 4 hours. The sintering holding time affects the density of the Mo metal skeleton, and further affects the strength and plasticity of the alloy. The present invention limits the sintering holding time to the above range, which is conducive to improving the density of the Mo metal skeleton.
[0044] In the present invention, the sintering is preferably pressureless sintering; the sintering atmosphere is preferably hydrogen, and the sintering gas pressure is preferably 0.1 MPa.
[0045] After obtaining the Mo metal skeleton, the present invention performs melt infiltration of pure Ce with the Mo metal skeleton to obtain a high-plasticity Mo-Ce impact energy release alloy.
[0046] The present invention has no special requirements for the infiltration equipment, as long as the infiltration process conditions are met. In the embodiment of the present invention, a vacuum furnace is preferably used.
[0047] In the present invention, the purity of the pure Ce is preferably above 99.9%.
[0048] In the present invention, the infiltration is preferably carried out under vacuum conditions, and the vacuum degree of the vacuum conditions is preferably less than 1Pa.
[0049] In the present invention, the infiltration temperature is preferably 800-1300°C, more preferably 1000-1300°C. The infiltration temperature affects the performance of the alloy. When the temperature is lower than 800°C, Ce is basically not melted and cannot be filled into the Mo metal skeleton as a melt; when the temperature is higher than 1300°C, the diffusion capacity of Mo atoms is enhanced, the skeleton will shrink, and it is easier to form closed pores, making it difficult to fill Ce. The present invention limits the infiltration temperature within the above range, which can well fill Ce into the Mo metal skeleton and is beneficial to improving the strength and plasticity of the alloy.
[0050] In the present invention, the infiltration is preferably performed by step heating; the step heating method is preferably to first heat to 700°C at a rate of 6-10°C / min, and then heat to the required temperature for infiltration at a rate of 1-3°C / min. When the temperature is below 700°C, Ce is in a solid state, and a higher heating rate can be used to reduce the heating time; when the temperature reaches 700°C, Ce gradually melts, and a slower heating rate is required to fully infiltrate Ce into the Mo metal skeleton.
[0051] In the present invention, the holding time of the infiltration is preferably 0.5 to 3 hours, more preferably 1 to 3 hours. The holding time of the infiltration affects the filling effect of Ce. When the holding time is less than 0.5 hours, it is difficult to fill Ce into the Mo metal skeleton, or the filling is uneven; the infiltration mainly relies on capillary force, and the whole is a relatively fast process. If the holding time is higher than 3 hours, it will cause a decrease in production efficiency and an increase in cost. The present invention limits the holding time of the infiltration to the above range, which can well fill Ce into the Mo metal skeleton and take into account the performance and production cost of the alloy.
[0052] After the pure Ce and Mo metal skeletons are infiltrated, the present invention preferably further comprises cooling the alloy, and the cooling is preferably furnace cooling.
[0053] The present invention can obtain a porous Mo skeleton with high strength by selecting powder of a certain particle size, adopting cold isostatic pressing process and sintering process. On the one hand, it can ensure that the material has high material strength after low-temperature infiltration, and on the other hand, it can obtain a Mo skeleton with fine pore size and high pore connectivity to provide capillary force of the infiltrate during the infiltration process, that is, to ensure the filling of molten Ce in the subsequent infiltration process, so as to obtain a high-density Mo-Ce alloy; since Mo and Ce do not react with each other, Ce exists in a single substance form, which can maximize the impact energy release activity of the Ce element. In addition, the Mo in the material is a body-centered cubic structure, and Ce is a face-centered cubic structure. Both have high plasticity, and both have good interface wettability, so that the material has high plasticity. This can ensure the high overload resistance of the material under shock wave loading conditions on the one hand, and on the other hand, it is conducive to the accumulation of plastic deformation work during high-speed impact to obtain high temperature rise, which is convenient for subsequent sufficient oxidation energy release.
[0054] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] Example 1
[0056] A high-plasticity Mo-Ce impact energy release alloy consists of a Mo metal skeleton and Ce filled in the Mo metal skeleton; wherein the high-plasticity Mo-Ce impact energy release alloy comprises 85wt% of Mo and 15wt% of Ce.
[0057] The preparation process is as follows:
[0058] (1) Powder screening: Use an 800-mesh sieve to screen Mo powder with a particle size of 10 μm to reduce the degree of agglomeration.
[0059] (2) Compression molding: The powder sieved in step (1) is placed in a rubber mold (2 cm in diameter and 10 cm in length), and is pressed by cold isostatic pressing at a pressure of 150 MPa and a holding time of 20 min to obtain a green body.
[0060] (3) Skeleton pre-sintering: The green body obtained by pressing in step (2) is placed in a sintering furnace for pressureless sintering at a sintering temperature of 1200°C for 2 hours and then cooled in the furnace; hydrogen at a pressure of about 0.1 MPa is introduced as a protective gas during the entire sintering process.
[0061] (4) Prepare high-purity Ce ingot.
[0062] (5) Infiltration: The pre-sintered skeleton and pure Ce ingot obtained in steps (3) and (4) are placed in a vacuum furnace for infiltration treatment. The infiltration process is as follows: (a) heating from room temperature to 700°C at a heating rate of 8°C / min; (b) heating from 700°C to 1100°C at a heating rate of 3°C / min; (c) keeping warm for 2h; (d) cooling with the furnace; the entire infiltration process is carried out under vacuum conditions with a vacuum degree of 1Pa.
[0063] Example 2
[0064] A high-plasticity Mo-Ce impact energy release alloy consists of a Mo metal skeleton and Ce filled in the Mo metal skeleton; wherein the high-plasticity Mo-Ce impact energy release alloy comprises 82wt% of Mo and 18wt% of Ce components.
[0065] The preparation process is as follows:
[0066] (1) Powder screening: Use a 700-mesh sieve to screen Mo powder with a particle size of 5 μm to reduce the degree of agglomeration.
[0067] (2) Compression molding: The powder sieved in step (1) is placed in a rubber mold (2 cm in diameter and 10 cm in length), and is pressed by cold isostatic pressing at a pressure of 250 MPa and a holding time of 10 min to obtain a green body.
[0068] (3) Skeleton pre-sintering: The green body obtained by pressing in step (2) is placed in a sintering furnace for pressureless sintering at a sintering temperature of 1300°C for 3 hours and then cooled in the furnace; hydrogen at a pressure of about 0.1 MPa is introduced as a protective gas during the entire sintering process.
[0069] (4) Prepare high-purity Ce ingot.
[0070] (5) Infiltration: The pre-sintered skeleton and pure Ce ingot obtained in steps (3) and (4) are placed in a vacuum furnace for infiltration treatment. The infiltration process is as follows: (a) heating from room temperature to 700°C at a heating rate of 6°C / min; (b) heating from 700°C to 1300°C at a heating rate of 2°C / min; (c) keeping warm for 3h; (d) cooling with the furnace; the entire infiltration process is carried out under vacuum conditions with a vacuum degree of 1Pa.
[0071] Example 3
[0072] A high-plasticity Mo-Ce impact energy release alloy consists of a Mo metal skeleton and Ce filled in the Mo metal skeleton; wherein the high-plasticity Mo-Ce impact energy release alloy comprises 90wt% of Mo and 10wt% of Ce components.
[0073] The preparation process is as follows:
[0074] (1) Powder screening: Mo powder with a particle size of 8 μm was screened using a 900-mesh sieve to reduce the degree of agglomeration.
[0075] (2) Compression molding: The powder sieved in step (1) is placed in a rubber mold (2 cm in diameter and 10 cm in length), and is pressed by cold isostatic pressing at a pressure of 250 MPa and a holding time of 30 min to obtain a green body.
[0076] (3) Skeleton pre-sintering: The green body obtained by pressing in step (2) is placed in a sintering furnace for pressureless sintering at a sintering temperature of 1500°C for 3 hours and then cooled in the furnace; hydrogen at a pressure of about 0.1 MPa is introduced as a protective gas during the entire sintering process.
[0077] (4) Prepare high-purity Ce ingot.
[0078] (5) Infiltration: The pre-sintered skeleton and pure Ce ingot obtained in steps (3) and (4) are placed in a vacuum furnace for infiltration treatment. The infiltration process is as follows: (a) heating from room temperature to 700°C at a heating rate of 9°C / min; (b) heating from 700°C to 1200°C at a heating rate of 2°C / min; (c) keeping warm for 1.5 h; (d) cooling with the furnace; the entire infiltration process is carried out under vacuum conditions with a vacuum degree of 1 Pa.
[0079] Example 4
[0080] A high-plasticity Mo-Ce impact energy release alloy consists of a Mo metal skeleton and Ce filled in the Mo metal skeleton; wherein the high-plasticity Mo-Ce impact energy release alloy comprises 95wt% of Mo and 5wt% of Ce components.
[0081] The preparation process is as follows:
[0082] (1) Powder screening: Use a 1000-mesh sieve to screen the Mo powder with a particle size of 7 μm to reduce the degree of agglomeration.
[0083] (2) Compression molding: The powder sieved in step (1) is placed in a rubber mold (with a diameter of 2 cm and a length of 10 cm), and is pressed by cold isostatic pressing at a pressure of 200 MPa and a holding time of 15 min to obtain a green body.
[0084] (3) Skeleton pre-sintering: The green body obtained by pressing in step (2) is placed in a sintering furnace for pressureless sintering at a sintering temperature of 1600°C for 4 hours and then cooled in the furnace; during the entire sintering process, hydrogen at a pressure of about 0.1 MPa is introduced as a protective gas.
[0085] (4) Prepare high-purity Ce ingot.
[0086] (5) Infiltration: The pre-sintered skeleton and pure Ce ingot obtained in steps (3) and (4) are placed in a vacuum furnace for infiltration treatment. The infiltration process is as follows: (a) heating from room temperature to 700°C at a heating rate of 10°C / min; (b) heating from 700°C to 1000°C at a heating rate of 1°C / min; (c) keeping warm for 1h; (d) cooling with the furnace; the entire infiltration process is carried out under vacuum conditions with a vacuum degree of 1Pa.
[0087] Test Example 1: Density and compactness test
[0088] Alloy density and density test:
[0089] Mo metal skeleton is a porous material. Generally, the density and compactness are not determined by the drainage method. Instead, a cylindrical sample of a certain standard size is cut, and the height and diameter of the standard sample are accurately measured multiple times with a vernier caliper to calculate the volume V. The mass m of the sample is measured with a precision balance, and then the theoretical density formula is used:
[0090] ρ=m / V,
[0091] The density of the sample is calculated, and then standard cylindrical samples cut from different positions are selected for repeated measurement and calculation. The average of all calculated densities is taken as the actual density of the skeleton. The actual density is divided by the theoretical density of the skeleton components to obtain the density of the porous skeleton. The porosity of the skeleton is obtained by subtracting the density from 1.
[0092] The density, compactness and porosity test results of the Mo metal skeletons prepared in Examples 1 to 4 are shown in Table 1:
[0093] Table 1 Density, compactness and porosity statistics of Mo metal skeleton
[0094]
[0095]
[0096] The actual density of the Mo-Ce alloy after infiltration was determined by the Archimedes drainage method. The instrument used was a Mettler-Toledo NewClassic balance with an accuracy of 0.1 mg. First, weigh the mass of the sample in the air, recorded as m0, then hang the sample in deionized water, weigh the mass of the sample in the water m1, and look up the table to obtain the density of water at the measurement temperature ρl, and substitute the obtained data into the formula:
[0097] ρ measured = m0*ρl / (m0-m1),
[0098] The actual density ρ of the alloy is obtained by actual measurement. The theoretical density of the alloy is based on the assumption that the infiltration phase Ce completely fills the pores of the skeleton. The volume ratio of Mo and Ce elements in the alloy can be known from the density and porosity of the skeleton, and then the theoretical density of the alloy is calculated. The actual density is divided by the theoretical density to obtain the final density of the alloy.
[0099] The compactness and density test results of the alloys prepared in Examples 1 to 4 are shown in Table 2:
[0100] Table 2 Density and density statistics of alloys
[0101] serial number Example 1 Example 2 Example 3 Example 4 <![CDATA[Actual density g / cm 3 > 9.21 9.17 9.45 9.77 <![CDATA[Theoretical density g / cm 3 > 9.47 9.33 9.71 9.96 Density 97.25% 98.28% 97.32% 98.09%
[0102] Test Example 2: SEM microstructure observation
[0103] The microstructure of the high plasticity Mo-Ce impact energy release alloy prepared in Example 2 was observed using a scanning electron microscope. Figure 1 Observation Figure 1 It can be seen that the alloy structure is uniform and dense, with almost no pores.
[0104] Test Example 3: Mechanical Properties Test
[0105] The high plasticity Mo-Ce impact energy release alloys prepared in Examples 1 to 4 were subjected to quasi-static compression tests using an electronic universal testing machine (model Instron 5985) at a test rate of 0.3 mm / min. The stress-strain curves were obtained using Origin software, as shown in FIG. Figure 2 As shown in the figure, it can be seen that the quasi-static compression critical failure strain of the alloy provided by the present invention is above 40%, and the alloy prepared in Example 4 is even above 50%, indicating that the alloy provided by the present invention has good quasi-static plasticity. The critical failure strain value is recorded in Table 3.
[0106] Table 3 Quasi-static compression test critical failure strain value record
[0107]
[0108]
[0109] The high plasticity Mo-Ce impact energy release alloys prepared in Examples 1 to 3 were subjected to dynamic compression tests using a split Hopkinson pressure bar (SHPB) at a strain rate of 3500 s -1 , using D-wave and Origin software, the stress-strain curve is obtained, such as Figure 3 As shown in the figure, it can be seen that the dynamic critical failure strain of the alloy is between 28% and 32%, indicating that the alloy provided by the present invention has good dynamic plasticity. The critical failure strain value is recorded in Table 4.
[0110] Table 4 Dynamic compression test critical failure strain value record
[0111] serial number Example 1 Example 2 Example 3 Compression strength MPa 709.5 733 686 Failure strain 30.4% 28.3% 33.2%
[0112] It can be seen from the above embodiments that the present invention uses Mo as a skeleton and Ce to fill the pores of the Mo skeleton, and the prepared Mo-Ce alloy has high density, strength and excellent plasticity.
[0113] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high plasticity Mo-Ce impact energy release alloy, comprising a Mo metal skeleton and Ce filled in the Mo metal skeleton, wherein the mass fraction of Mo in the high plasticity Mo-Ce impact energy release alloy is 50-95%, and the mass fraction of Ce is 5-50%.
2. The high plasticity Mo-Ce impact energy release alloy according to claim 1, characterized in that: The density of the Mo metal skeleton is 7.5-9.5 g / cm 3 , the density is 73~93%.
3. The high plasticity Mo-Ce impact energy release alloy according to claim 1, characterized in that: The density of the high plasticity Mo-Ce impact energy release alloy is 8-10 g / cm 3 , density is greater than 97%.
4. The method for preparing the high plasticity Mo-Ce impact energy release alloy according to any one of claims 1 to 3, characterized in that: The steps include: 1) Pressing Mo metal powder into a green body; 2) sintering the green body obtained in step 1) to obtain a Mo metal skeleton; 3) Infiltrating pure Ce with the Mo metal skeleton obtained in step 2) to obtain a high-plasticity Mo-Ce impact energy release alloy.
5. The preparation method according to claim 4, characterized in that: In the step 1), the particle size of the Mo metal powder is 5 to 10 μm.
6. The preparation method according to claim 4, characterized in that: The pressing and molding in step 1) adopts a cold isostatic pressing process, the pressure of the cold isostatic pressing process is 150-400 MPa, and the holding time is 5-30 minutes.
7. The preparation method according to claim 4, characterized in that: In the step 2), the sintering temperature is 1200-1800° C., and the holding time is 2-6 hours.
8. The preparation method according to claim 4, characterized in that: The infiltration in step 3) is carried out under vacuum conditions, with a vacuum degree of less than 1 Pa.
9. The preparation method according to claim 4 or 8, characterized in that: In the step 3), the infiltration temperature is 800-1300° C., and the insulation time is 0.5-3 h.
10. The preparation method according to claim 4 or 8, characterized in that: The infiltration in step 3) is performed by step heating; the step heating method is to first heat the temperature to 700°C at a rate of 6-10°C / min, and then heat the temperature to the infiltration temperature at a rate of 1-3°C / min.